Beauty and the Beast of Advertising: The impact of idealized images of physical attractiveness on consumer behavior and well- being. - Nair, Samyukta (2007)
It appears that the idea of beauty in today's day and age has been replaced by a narrower definition that is largely located in limited ideals of physical appearance and powerfully communicated through advertising, an important agent of socialization. (Ecoff et al, 2004: 47)It has been hypothesized that images of physical attractiveness present in advertisements are unrealistic, influence and idealize size, shape and propagate the beauty myth within society. These cultural notions of the body beautiful are said to be disorder-producing, causing bodily dissatisfaction, chronic dieting and eating disorders amongst other things.Moreover, literature suggests discrepancies to exist in the perception of beauty images in advertisements amongst male and female consumers. The present study wishes to explore the broader context of this important and controversial issue and answer questions relating to how and to what degree advertising involving thin/attractive endorsers affect consumers within the UK, if at all. It attempts to identify whether any discrepancies existed amongst male and female consumers with regard to the perception of beauty images in advertisements and consumer viewpoints with regard to the advertising being a reflector and reinforcer of social values, especially with regard to beauty and physical attractiveness.Through the use of a self-administered questionnaires, which contained the Body Esteem Scale (Franzoi & Shields, 1984) the parameteres discussed above were explored. Though findings were not congruent with all the hypotheses, it was found that consumers held advertisements to be an important source of information about being attractive, one that objectified the human body and promoted unrealistic standards of beauty within society. On viewing adverts constaining images of idealized physical attractiveness, pressure to exercise, change physical appearance and low body esteemwere the only effects identified. Moreover, consumers were found to be of the opinion that both men and women are equally faced with unrealistic expectations of physical attractiveness. Additionally, findings supported the hypothesis of advertising being an important agent of socialization, one which reiforces, reflects, mirrors and shapes values within society especially highlights people's preoccupation with the importance of physical attractiveness.